Pluripotential mesenchymal cells repopulate bone marrow and retain osteogenic properties. - Dahir, G; Cui, Q; Anderson, P; Simon, C; Joyner, C; Triffitt, J; Balian, G (2000)
Precursor cells, isolated from bone marrow, can develop into various cell types and may contribute to skeletal growth, remodeling, and repair. The D1 cell line was cloned from a multipotent mouse bone marrow stromal precursor and has osteogenic, chondrogenic, and adipogenic properties. The osteogenic phenotype of these precursor cells is relevant to the process of fracture healing and osteointegration of prosthetic implants. The D1 cells were labeled genetically using a replication incompetent retroviral vector encoding beta-galactosidase, an enzyme which is used as a marker. Labeled cells are readily identifiable by staining with 5-bromo-4-chloro-3-indoyl-beta-D-galactoside and by flow cytometry, and retain the desired osteogenic characteristics in vivo as shown by von Kossa staining, alkaline phosphatase assay, an increase in cyclic adenosine monophosphate in response to parathyroid hormone, osteocalcin messenger ribonucleic acid production, and bone formation in diffusion chambers. In addition, the cells cloned from marrow stroma repopulate the marrow of host mice, persist for several weeks, and retain their osteogenic potential ex vivo. The data suggest that such cells may be used to replenish the number of osteoprogenitors in marrow, which appear to decrease with age, thereby leading to recovery from bone loss and improved bone growth and repair. Labeling these cells creates a model in which to study the potential of such cells to participate in fracture repair, ingrowth around prosthetic implants, treatment of osteoporosis, and to explore the possibility of gene delivery to correct mutations or defects in metabolism that are responsible for certain skeletal abnormalities.